Therapeutic Applications of Terpenes on Inflammatory Diseases - Del Prado-Audelo, María Luisa; Cortés, Hernán; Caballero-Florán, Isaac H.; González-Torres, Maykel; Escutia-Guadarrama, Lidia; Bernal-Chávez, Sergio A.; Giraldo-Gomez, David M.; Magaña, Jonathan J.; Leyva-Gómez, Gerardo (Frontiers in Pharmacology, 2021)
In the last decades, the search for natural products with biological applications as alternative treatments for several inflammatory diseases has increased. In this respect, terpenes are a family of organic compounds obtained mainly from plants and trees, such as tea, cannabis, thyme, and citrus fruits like lemon or mandarin. These molecules present attractive biological properties such as analgesic and anticonvulsant activities. Furthermore, several studies have demonstrated that certain terpenes could reduce inflammation symptoms by decreasing the release of pro-inflammatory cytokines for example, the nuclear transcription factor-kappa B, interleukin 1, and the tumor necrosis factor-alpha. Thus, due to various anti-inflammatory drugs provoke side effects, the search and analysis of novel therapeutics treatments are attractive. In this review, the analysis of terpenes’ chemical structure and their mechanisms in anti-inflammatory functions are addressed. Additionally, we present a general analysis of recent investigations about their applications as an alternative treatment for inflammatory diseases. Furthermore, we focus on terpenes-based nanoformulations and employed dosages to offer a global perspective of the state-of-the-art.